Economic Value of Florida Water Resources: Contributions of Tourism and Recreation to the Economy - Tatiana Borisova; Kurt Oehlbeck; Xiang Bi; Tara Wade; Alan Hodges; Kelly Grogan; Fe Hei (EDIS, 2020)
This paper is a part of the EDIS series “Economic Value of Florida Water Resources” and it presents results from economic studies examining benefits from water-based recreation in Florida. Our special focus is freshwater-based recreation. Specifically, studies examining the “economic contribution” or “economic impact” of recreation activities around various natural sites are discussed. Interested reader can pick and choose the studies most relevant to his/her area of interests or those discussing recreational sites nearby. https://edis.ifas.ufl.edu/fe1065